Enhancement stiffness properties of asphalt using recycled HDPE (high density polyethylene) as additive and using several of mineral filler (portland cement and lime) on wearing course - Siti Umirah, Kamarudin (2014)
The increase in traffic growth nowadays need high maintenance expenditures because demands the urgent for building better, long-lasting and more efficient roads to prevent and minimize bituminous pavement distresses. The aim for this research is to determine the parameter of asphalt mixture properties as follow the requirement hot mix asphalt wearing course (ACW 14) in Standard Specification of Public Work Department Road Work. The investigate on the stiffness properties of HDPE as partial coarse aggregate additive and using several of mineral filler (Portland cement and lime) on wearing course by using Indirect Tensile Stiffness Modulus testing (ITSM) at 20°C. The different percentage of asphalt mixture HDPE were added in asphalt mixture such as 2%, 4 %, 8 % and 10%. In this experimental, for mineral filler that were used is lime and Portland cement. The result obtained from the lab testing, all the material was archive to use in asphalt mixture. The maximum stiffness of modified asphalt mixture reach at 4% additive with recycled HDPE and 7% lime as mineral filler.